Adsorption of Crystal Violet onto Adsorbents Derived from Agricultural Wastes: Kinetic and Equilibrium Studies - LK Akinola; AM Umar (Journal of Applied Sciences and Environmental Management)
Suitability of adsorbents derived from groundnut shell (GS) and bean pod (BP) in removing crystal violet from aqueous solution was evaluated in a series of batch experiments. Findings reveal that the points of zero charge (PZC) of GS and BP are 3.50 and 3.00 respectively. Findings also show that GS and BP exhibit maxima adsorption at pH values of 6.00 and 5.00 respectively. For both GS and BP, pseudo-second order model gives the best fit for the sorption kinetic data while Freundlich isotherm gives the best fit for the sorption equilibrium data. These findings suggest that the adsorption of crystal violent onto GS and BP probably involves chemisorption and the adsorption does not reach a plateau as the concentration of crystal violet in the aqueous solution increases. This study demonstrates the suitability of GS and BP as low-cost adsorbents for removing crystal violet from industrial wastewater.